Effective inhibition of PBPs by cefepime and zidebactam in the presence of VIM-1 drives potent bactericidal activity against MBL-expressing Pseudomonas aeruginosa. (21st February 2020) - Moya, Bartolome; Bhagwat, Sachin; Cabot, Gabriel; Bou, German; Patel, Mahesh; Oliver, Antonio
Abstract: Objectives: The combination of cefepime and the novel β-lactam enhancer zidebactam (WCK 5222) is under development for the treatment of difficult-to-treat Gram-negative infections. Against MBL-producing pathogens, cefepime and zidebactam induce cell elongation and spheroplast formation, indicating PBP3 and PBP2 dysfunction, respectively, having a potent bactericidal effect as a combination. The objective of the present study was to determine the mechanistic basis of the bactericidal effect of cefepime/zidebactam on MBL-expressing pathogens. Methods: Pseudomonal PBP-binding affinities of cefepime, zidebactam and imipenem were assessed at different timepoints and also in the presence of purified VIM-1 using a Bocillin FL competition assay. The antibacterial activity of cefepime/zidebactam against three VIM-expressing Pseudomonas aeruginosa isolates was assessed by time–kill and neutropenic mouse lung/thigh infection studies. Results: Amidst cefepime-hydrolysing concentrations of VIM-1, substantial cefepime binding to target PBPs was observed. High-affinity binding of zidebactam to PBP2 remained unaltered in the presence of VIM-1; however, MBL addition significantly affected imipenem PBP2 binding. Furthermore, the rate of cefepime binding to the primary target PBP3 was found to be higher compared with the imipenem PBP2 binding rate. Finally, complementary PBP inhibition by cefepime/zidebactam resulted in enhanced bactericidal activity in time–kill and neutropenic mouse lung/thigh infection studies against VIM-6-, VIM-10- and VIM-11-expressing P. aeruginosa, thus revealing the mechanistic basis of β-lactam enhancer action. Conclusions: For the first time ever (to the best of our knowledge), this study demonstrates that in the presence of VIM-1 MBL, β-lactamase-labile cefepime and β-lactamase-stable zidebactam produce effective inhibition of respective target PBPs. For cefepime, this seems to be a result of a faster rate of PBP binding, which helps it overcome β-lactamase-mediated hydrolysis.